Is beauty-based inequality gendered? A systematic review of gender differences in socioeconomic outcomes of physical attractiveness in labor markets - Kukkonen Iida; Pajunen Tero; Sarpila Outi; Åberg Erica (Taylor and Francis Group, 2025)
During the past decade, academic interest in physical attractiveness-based social inequalities has spread significantly beyond the United States to Europe. In previous research, however, there has been no consensus on whether the socioeconomic outcomes of physical attractiveness are gendered. Thus, we conducted a systematic review to determine to what extent and how the socioeconomic outcomes of physical appearance in labor markets are gendered. A total of 58 articles were reviewed after searching through five databases and identifying relevant articles. The results show that, in general, more attractive individuals are socioeconomically favored, which is true for both men and women. The number of studies that claim that attractiveness is more beneficial for women is almost equal to the number of studies that claim it is more beneficial for men. Moreover, while the socioeconomic outcomes for men are somewhat consistent, the outcomes for women appear to be more inconsistent; only women appear to be both rewarded and penalized for being attractive. Therefore, we conclude that contextual factors play a greater role in attractiveness-related outcomes, especially for women, than previously assumed.